Competent uses of competence: on the difference between a value-judgment and empirical assessability - Birgit Schaffar (Taylor & Francis Group, 2021)
This article considers the concept of Competence as applied to educational theory and policy, and illuminates the possibility of significant variations in meaning. Referring to Wittgenstein's distinctions between transitive and intransitive uses of notions and Holland's description of mastery, the article argues in favour of two senses in which someone can be described as being competent: i) as expressive of a value judgment; and ii) as pointing to a person's (formal) qualifications. While the latter opens a path towards different forms of measurements of competence, being competent as a value judgment eludes any such treatment. Making this distinction, it is argued that competence is a less illuminative theoretical term than, for example, the pair of concepts Bildung versus Ausbildung ((self-)subjectivation vs training), that has been used in the Continental tradition in order to describe a similar distinction. With examples from educational contexts, the article demonstrates that the moment educational theory is using one word for two meanings, this central distinction in education is either concealed or forgotten. Focusing on competence purely as an empirically assessable notion risks playing into the hands of instrumentalising education.